Unblinded and blinded N-of-1 trials versus usual care: a randomized controlled trial to increase statin uptake in primary care - Tudor, K; Brooks, J; Howick, J; Fox, R; Aveyard, P (American Heart Association, 2022)
Background: The aim was to assess whether an intervention incorporating a practicable open-label n-of-1 trial would lead to greater uptake of statin than usual care and comparable uptake to a closed-label gold-standard n-of-1 trial.